Study on the Beneficiation-Metallurgy Process on an Argillaceous High Oxidation Gold in Henan Province - Ning Yang (Kuangchan zonghe liyong, 2022)
A gold in Henan Province is a complex and argillaceous high oxidation gold mines, and it has the characteristics of complex embedment characteristics, high oxidation rate and serious argillization, which lead to the poor beneficiation indexes . In order to improve the beneficiation recovery rate of this kind of ore, a detailed test was carried out. The results show that it is difficult to obtain a good leaching index by single leaching process or pre-oxidation-leaching process, and the leaching rate is 77.46% and 80.28%; The leaching index can be significantly improved to 93.66% by roasting-leaching process, but the technical economy is poor. A good total recovery indexes of 94.25% can be obtained by flotation-leaching process, which is highly operable. Therefore, the flotation-leaching process has good adaptability to this kind of ore, which can not only recover the ultra-fine particle gold highly dispersed in sulfide and gangue minerals, but also recover the medium and coarse particle gold. This study provides a reference for the production practice of mining enterprises.